ANALISIS KOMPETENSI PEDAGOGIK DALAM MENINGKATKAN KINERJA GURU DI SD NEGERI - Yuliana, Yuliana; Zahriyanti, Zahriyanti; Najmuddin, Najmuddin (Hijri, 2024)
This research aims to (1) Find out the principal's strategy in formulating the development of school policies that care and have an environmental culture to implement a go green-based school at State Elementary School 01 Meulaboh, West Aceh, (2) Find out the principal's strategy in developing an environmentally based curriculum to implement go green based school at State Elementary School 01 Meulaboh West Aceh, (3) Knowing the principal's strategy in developing participatory based activities to implement a go green based school at State Elementary School 01 Meulaboh and (4) Knowing the school principal's strategy in developing and managing school support facilities to implement a go green-based school at State Elementary School 01 Meulaboh, West Aceh. This research uses qualitative methods. The research findings were obtained (1) Planning for the development of pedagogical competence at SDN Meunasah Ara and SDN Peureumbe, through the preparation of RPPs and syllabi based on the independent curriculum, provides a strong foundation for more structured and relevant learning, which directly supports teacher performance in managing classes and delivering materials effectively and inclusive learning that is relevant to students' needs (2) Implementation of pedagogical competency development carried out by principals, deputy principals and teachers at SDN Meunasah Ara and SDN Peureumbe really supports performance improvement Teacher. Through innovation in learning methods, personal approaches to students, as well as ongoing supervision and training, they are able to create an effective learning environment, which ultimately has a positive impact on improving the quality of learning in the school as well as improving teacher performance (3) Evaluation of the development of pedagogical competence in Kaway XVI District Elementary School, West Aceh has been implemented well, although assessment techniques need to be more varied. Training related to assessment has been carried out, but there needs to be further improvement in facilities and assistance that supports teacher performance in designing teaching that is more effective and responsive to student development, (4) Follow-up to the development of pedagogical competence at SDN Meunasah Ara and SDN Peureumbe involves collaborative learning, intensive mentoring, and the use of technology in project- based assessments. Teachers at both schools routinely analyze assessment results to determine student potential, although most do not involve much student input in learning reflection. Remedial is one of the follow-up actions carried out by teachers to improve the quality of teaching, teacher performance and help students who are having difficulties..